Research on Gang-Related Violence in the 21st Century - Valasik, Matthew; Reid, Shannon E. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Conflict, including the threat or fear of potential violence, or being witness to or a victim of physical violence, constantly surrounds gangs and their communities and is the principal driver sustaining gang life. This Special Issue examines the diverse nature of gang-related violence with the goal of better understanding the growing complexities of gang violence over the last two decades to better inform public policy solutions. The contributions included in this Special Issue highlight the complex nature of gang-related violence in the 21st Century. As much as policy makers, the media, and even scholars like to simplify gang-related violence, all of the studies included in this Special Issue highlight the nuance and variation that exists.